2009
DOI: 10.1080/09712119.2009.9707058
|View full text |Cite
|
Sign up to set email alerts
|

Some Histological and Physiological Features of Avian Kidney

Abstract: Nabipour, A., Alishahi, E. and Asadian, M. 2009. Some histological and physiological features of avian kidney. J. Appl. h i m . Res.,.The detailed histology of the kidney was studied i n rock dove, collared dove and owl (3 each). Each kidney consisted of a caudal, a middle and a cranial division. The cortex made up the vast majority of the kidney with only a small portion as medulla. They were arranged in cones of different lengths, which were distributed randomly within the kidney. Medullary nephron tubules w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 5 publications
13
14
0
1
Order By: Relevance
“…In the present result the intermediate type of corpuscle was not observed, this result was as well that of the previous study by (Sivakumar et al, 2012) the intermediate type of corpuscle has recorded by (Mobini and Abdollahi, 2016) in Japanese quail and by (Abood et al, 2014) in Chick &harrier, the reptilian type of renal corpuscles might limit the capacity of the kidney produce hyperosmotic urine and the mammalian corpuscles are essential for concentrated urine (Nishimura and Fan, 2003), this result suggest that, much of the mammalian and intermediate types of corpuscles in breeds are related with birds food habits, so these nephrons play an important role conserving body water. The structure of renal corpuscle was similar to those results mentioned by (Nabipour, 2009, Abood et al, 2014.Other cortical region components were proximal convoluted tubules, distal convoluted tubules, collecting tubules and per lobular collecting ducts along with the many peritubular capillary sinuses, this results concurs (Al-Ajeely and Mohammed, 2012;Sivakumar et al, 2012;Abood et al, 2014;Michalek et al, 2016), (Nabipouret al, 2009).In our results the pariet al layer of Bowman's capsule and the endothelial cells of the capillary tuft basement membranes were delicate structure that reacted positive with PAS stain as described by Sivakumar et al, (2012) in birds and El -Daly(2013) in mammals, this suggested that, the neutral pH of delicate basement membranes of capillaries lead to extruding a fluid from plasma with its electrolyte and water composition as the glomerular filtrate (Cunningham & Klein, 2007). The present result revealed the cytoplasm of epithelial cells and the lumen of proximal convoluted tubules contained positive PAS substances, that indicated the presence of neutral glycoprotein in this part of nephron, this result accord with result revealed that, in of rock dove the lumen of the proximal convoluted tubules contained PAS positive substances (Nabipour 2009;Sivakumar et al, 2012;Sreeranjini et al, 2000;Mobini & Abdollahi, 2016), also this result is compatible with result of (Brandon et al, 2009) in Juvenile American Alligator.On the other hand results of El -Daly,(2013) concluded that, the carbohydrates and proteins have increased after nephrone compartments (glomeruli, basement membrane of the tubules and brush border of proximal tubules) have exposed for green tea in compared to that group which exposed to harmful exogenous substances, this elevation could be due to an increase in the re-absorption of kidney tubules or might be due to an increase in glycogen synthesis or a decrease in glycogen breakdown by phosphorylase, which causes a glycogen recovery in the tissue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present result the intermediate type of corpuscle was not observed, this result was as well that of the previous study by (Sivakumar et al, 2012) the intermediate type of corpuscle has recorded by (Mobini and Abdollahi, 2016) in Japanese quail and by (Abood et al, 2014) in Chick &harrier, the reptilian type of renal corpuscles might limit the capacity of the kidney produce hyperosmotic urine and the mammalian corpuscles are essential for concentrated urine (Nishimura and Fan, 2003), this result suggest that, much of the mammalian and intermediate types of corpuscles in breeds are related with birds food habits, so these nephrons play an important role conserving body water. The structure of renal corpuscle was similar to those results mentioned by (Nabipour, 2009, Abood et al, 2014.Other cortical region components were proximal convoluted tubules, distal convoluted tubules, collecting tubules and per lobular collecting ducts along with the many peritubular capillary sinuses, this results concurs (Al-Ajeely and Mohammed, 2012;Sivakumar et al, 2012;Abood et al, 2014;Michalek et al, 2016), (Nabipouret al, 2009).In our results the pariet al layer of Bowman's capsule and the endothelial cells of the capillary tuft basement membranes were delicate structure that reacted positive with PAS stain as described by Sivakumar et al, (2012) in birds and El -Daly(2013) in mammals, this suggested that, the neutral pH of delicate basement membranes of capillaries lead to extruding a fluid from plasma with its electrolyte and water composition as the glomerular filtrate (Cunningham & Klein, 2007). The present result revealed the cytoplasm of epithelial cells and the lumen of proximal convoluted tubules contained positive PAS substances, that indicated the presence of neutral glycoprotein in this part of nephron, this result accord with result revealed that, in of rock dove the lumen of the proximal convoluted tubules contained PAS positive substances (Nabipour 2009;Sivakumar et al, 2012;Sreeranjini et al, 2000;Mobini & Abdollahi, 2016), also this result is compatible with result of (Brandon et al, 2009) in Juvenile American Alligator.On the other hand results of El -Daly,(2013) concluded that, the carbohydrates and proteins have increased after nephrone compartments (glomeruli, basement membrane of the tubules and brush border of proximal tubules) have exposed for green tea in compared to that group which exposed to harmful exogenous substances, this elevation could be due to an increase in the re-absorption of kidney tubules or might be due to an increase in glycogen synthesis or a decrease in glycogen breakdown by phosphorylase, which causes a glycogen recovery in the tissue.…”
Section: Discussionsupporting
confidence: 89%
“…The avian kidneys have differed from those of other mammal species, the avian kidney consists of three separated lobes (Nabipour, et al, 2009) (Mobini and Abdollahi, 2016). Avian kidney characterized by relatively long medulla that surrounded by the cortex and forming many of renal cones (Abood et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most unique features of avian kidneys is the presence of two types of nephrons, reptilian (or cortical type) and mammalian (or medullary) types (Abdul-Gahaffor et al, 2012;Bacha & Bacha;Dhyaa et al, 2014;Mobini & Abdollahi). In birds, only about 10 to 30 % of the nephrons are of the mammalian type (Nabipour et al, 2009;Abdul-Gahaffor et al;Mobini & Abdollahi). Since birds have primarily reptilian type nephrons, which produce isosmotic urine, urine concentration is limited.…”
Section: Introductionmentioning
confidence: 99%
“…gracilis . However, considering that morphological features of ECCs are similar to other well‐documented cell types involved in ion transport among vertebrates, such as kidney proximal tubular cells of teleosts and other vertebrates (Khalef & Ata, 2010; Morovvati et al, 2012; Morrison et al, 2007; Nabipour et al, 2009), and striated ducts cells of the salivary glands of mammals (Hand et al, 1999; Young & van Lennep, 1979), a function related to the ionic interchange between blood and gonoductal lumen could not be ruled out for this secretory cells.…”
Section: Discussionmentioning
confidence: 85%